Studentification as a New Form of Gentrification: Changing Neighborhood Dynamics in Bosna Hersek Neighborhood (Konya) - Tuncer, Tugba; Islam, Tolga (KARE PUBL, 2017)
The effects of studentification on neighborhoods are similar to those of the traditional gentrification processes: The concentration of students in a certain locality increases housing prices and transforms the socio-cultural base of the neighborhood in accordance with the preferences and needs of newcomers (university students). The neighborhood pattern that emerged following the studentification process in Bosna Hersek, a neighborhood located adjacent to Selcuk University - the second-largest university in Turkey by enrollment, was similar to many other gentrified areas: real estate values rose, the residential and commercial structure of the neighborhood has been reshaped according to the needs of the newcomers, the neighborhood has become dominated by a single social group (university students), and the incumbent population is being displaced socio-culturally (indirect displacement), if not physically (direct displacement). In this neighborhood, where students and non-students often live parallel lives that do not intersect with each other, the areas where these 2 groups do intersect have the potential to generate new lines of tension. As observed in many examples elsewhere in the world, topics such as noise, anti-social behaviors, and student lifestyle lay at the center of tensions between these 2 groups. Yet, students who were seen as unwelcome outsiders in the eyes of the incumbent residents in the early stages of studentification, have begun to be seen as preferred outsiders in the later stages, once the students gained numerical supremacy and their contributions to the economy of the neighborhood became perceptible by the incumbents. Bosna Hersek has transformed into a student ghetto, where the segregation between students and non-students and the numerical and cultural domination of the former group is easily observed. This new studentification-led form of segregation currently constitutes the main wave of gentrification in the Anatolian cities of Turkey.
Keywords: Gentrification; studentification; segregation; indirect displacement; student neighborhood; GEOGRAPHIES; STUDENTS; CITY; IMPACTS; CITIES; Public Administration